MYCN-driven regulatory mechanisms controlling LIN28B in neuroblastoma. Issue 1 (28th September 2015) - Beckers, Anneleen; Van Peer, Gert; Carter, Daniel R.; Gartlgruber, Moritz; Herrmann, Carl; Agarwal, Saurabh; Helsmoortel, Hetty H.; Althoff, Kristina; Molenaar, Jan J.; Cheung, Belamy B.; Schulte, Johannes H.; Benoit, Yves; et al.
Highlights: An unbiased LIN28B 3′UTR-miRNA library screen identifies 28 miRNAs targeting LIN28B. miR-26a-5p and miR-26b-5p are top candidate LIN28B-targeting miRNAs in neuroblastoma. Overexpression of miR-26a-5p or miR-26b-5p reduces LIN28B expression. MYCN does not inhibit transcription of mir-26, yet mature miR-26 miRNAs are downregulated in MYCN-driven neuroblastoma. MYCN induces LIN28B expression in neuroblastoma cells. Abstract: LIN28B has been identified as an oncogene in various tumor entities, including neuroblastoma, a childhood cancer that originates from neural crest-derived cells, and is characterized by amplification of the MYCN oncogene. Recently, elevated LIN28B expression levels were shown to contribute to neuroblastoma tumorigenesis via let-7 dependent de-repression of MYCN. However, additional insight in the regulation of LIN28B in neuroblastoma is lacking. Therefore, we have performed a comprehensive analysis of the regulation of LIN28B in neuroblastoma, with a specific focus on the contribution of miRNAs. We show that MYCN regulates LIN28B expression in neuroblastoma tumors via two distinct parallel mechanisms. First, through an unbiased LIN28B-3′UTR reporter screen, we found that miR-26a-5p and miR-26b-5p regulate LIN28B expression. Next, we demonstrated that MYCN indirectly affects the expression of miR-26a-5p, and hence regulates LIN28B, therefore establishing an MYCN-miR-26a-5p-LIN28B regulatory axis. Second, we provide evidence that MYCN regulates LIN28B expression via interaction with the LIN28B promoter, establishing a direct MYCN-LIN28B regulatory axis. We believe that these findings mark LIN28B as an important effector of the MYCN oncogenic phenotype and underline the importance of MYCN-regulated miRNAs in establishing the MYCN-driven oncogenic process.